Risk Management of Civil Projects by Using Fuzzy Logic - Amini, Amin (Curtin University, 2017)
This study identifies and classifies the risks that affect oil & gas projects and involves the vague and imprecise knowledge of experts in various fields of oil & gas industry to introduce a model based on fuzzy inference system for risk management. This model evaluates the probability and consequence of risk parameters and determines the magnitude of risk factors that affect the objectives of oil & gas construction projects including scope, cost, quality and time.